What promotes social and emotional wellbeing in Aboriginal and Torres Strait Islander children? Lessons in measurement from the Longitudinal Study of Indigenous Children - Marmor, A; Harley, D; Harley, David; Marmor, Alexandra (My University, 2018)
Though social and emotional wellbeing is an important outcome for policy makers in health and education, it is not adequately reflected by mainstream mental health assessment tools - in particular for Aboriginal and Torres Strait Islander families. This article aims to identify the early childhood factors associated with later social and emotional wellbeing when the child is ready to start school, and to develop a new indicator that could capture a more holistic view of wellbeing. It draws on data from the Longitudinal Study of Indigenous Children to look at selected individual and family factors during pregnancy and up to two years of age compared to children’s prosocial behaviour, mental health, connectedness, and other surrogate proxies for social and emotional wellbeing at school commencement. Though the authors were unable to create a single index of social and emotional wellbeing, the findings highlight the need to apply caution in applying Western biomedical health and wellbeing measures to Indigenous concepts and states.
Keywords: Culture -- Indigenous; Children -- Indigenous; Child Development -- Emotional; Childhood and child development; Culture; Children; Child Development; Emotional; Indigenous; Childhood and child development